Implementation of Argumentation-Based Problem-Based Learning Models to Improve Critical Thinking Skills in Vibration and Wave Material - Ahmad Farisi; Evendi Evendi; Abdul Halim; Muhammad Syukri; Elisa Elisa (Jurnal Penelitian Pendidikan IPA, 2023)
The demands of 21st-century skills are critical thinking skills and scientific literacy skills. In fact, from the results of observations and interviews conducted at MTsS Nurul Falah school, it was found that students critical thinking skills and scientific literacy skills were still low. The purpose of this study was to analyze students' critical thinking skills. students on vibration and wave material taught by the argumentation-based PBL model at MTsS Nurul Falah. This study uses a quasi-type quantitative approach experiment with the Non-Equivalent Control Group Design research design. The population used in this study were all students of class VIII. And the sample used purposive sampling techniques determined based on initial test scores when students first enter the school. Based on these considerations, class VIII-A with a total of 27 students was selected as the control class and class VIII-C with a total of 26 students was selected as the experimental class. The instrument used in this research is test questions in the form of essays. The research data were analyzed using the average test, N-gain, and independent sample t-test. The results showed that the average critical thinking value of the experimental class was in the high category and the control class was in the medium category. Based on the independent sample t-test, it was found that there was a significant difference in improving students' critical thinking skills and students' scientific literacy abilities on vibration and wave material taught using the argumentation-based PBL model at MTsS Nurul Falah.